Pengaruh Pemasaran Digital Dan Inovasi Layanan Terhadap Minat Beli Batik Tradisional Cirebon Dengan Nilai Pelanggan Sebagai Variabel Intervening: Studi Empirik: Batik Trusmi Cirebon - Dananjaya; Miranda, Agustinus; Thalib, Supriadi (CV ODIS, 2024)
The purpose of this research is to determine and analyze the influence of digital marketing and service innovation on interest in buying traditional Cirebon batik with customer value as an intervening variable. This research was conducted on Trusmi batik with respondents in the Cirebon area. This research category uses descriptive methods with a quantitative method approach. The sampling technique used purposive sampling with a total sample of 215 respondents. Data collection uses a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed with Smart PLS 3.0. The research results prove that digital marketing variables and service innovation have a significant effect on customer value. Then customer value also has a significant effect on purchasing interest. Furthermore, digital marketing and service innovation also have a significant influence on consumer buying interest. Complementary customer value variables can mediate the influence of digital marketing on purchasing interest. Likewise, customer value can complementaryly mediate the influence of service innovation on purchasing interest